(untitled) (Journal of Soft Computing Exploration, 2025)
Flooding is a serious threat in the Belik River area, Yogyakarta, especially during high rainfall and blocked water flow, while the existing Early Warning System (EWS) managed by BPBD Yogyakarta is still not functioning optimally. This study aims to design and implement a real-time water level monitoring system that can be used as an early warning system for flooding. The research method uses a Waterfall approach that includes the stages of requirements, design, implementation, testing, and operation and maintenance. The developed system is based on the Internet of Things (IoT) using HC-SR04 ultrasonic sensors and NodeMCU ESP32 microcontrollers connected to Firebase for data storage, visualized through a website, and equipped with automatic notifications via the Telegram application. The system was implemented at two points on the Belik River, Yogyakarta, with water level data recorded every minute for 3 hours over three days. The data obtained was pre-processed by averaging the sensor readings and ignoring abnormal data to improve stability. Evaluations were carried out on sensor accuracy, data transmission stability, real-time display on the website, and Telegram notification speed. The results of the study showed an average measurement error of 1.27%, with a tendency for the error to increase at distances greater than 300 cm. This system has proven capable of providing rapid information to the Regional Disaster Management Agency (BPBD) and the surrounding community to take early anticipatory measures against potential flooding, thereby helping to reduce the impact of losses and speed up emergency response.